Nurturing nutrition: Evidence from a randomized trial of structured electronic food vouchers in the Philippines - David A. Raitzer; Rita Abdel Sater; Odbayar Batmunkh; Julia Girard; Lennart Reiners; Amir Jilani (Asian Development Bank (ADB), 2025)
We present the findings of a pilot that randomized provision of structured electronic food vouchers to poor households in the Philippines, which was designed to inform a new national food voucher program. The study utilized a matched pair cluster-randomized controlled trial to evaluate the effectiveness of vouchers plus nutrition education sessions. It involved 4,883 poor households across five provinces, randomly assigned to the control group or to receive nutrition education and monthly electronic food vouchers worth PHP3,000 (55) with pre-allocated shares for different food groups. After 6 months, statistically significant improvements are found in household food expenditure, dietary diversity, and food security, although the dietary and food security effects are modest on average. Food expenditure responses to voucher allocations are strongest for proteins and for fruits and vegetables, whereas the carbohydrate allocations are more fungible. Notably, dietary effects are more pronounced in highly urban areas, in households enrolled in an existing conditional cash transfer program, in those with better nutrition knowledge at baseline, in smaller-sized households, and in those that had more recently redeemed the voucher. This suggests that effectiveness could be enhanced by adjusting voucher allocation ratios towards underconsumed food groups, increasing the voucher amount, increasing redemption frequency, and improving nutrition education.
Keywords: I12; I18; H23; I38; 330; food assistance; electronic food vouchers; nutrition; social protection